2021
DOI: 10.1002/nop2.1075
|View full text |Cite
|
Sign up to set email alerts
|

Mattering perception, work engagement and its relation to burnout amongst nurses during coronavirus outbreak

Abstract: Coronavirus is a communicable disease that originates from a large family of viruses that causes the diseases. It is also complicated by the fact that patients may have irregular symptoms. This means COVID-19 exhibits clinical presentations ranging from asymptomatic to acute respiratory distress syndrome and multiple-organ failure that leading to death. In addition, COVID-19 also is transmitted from person to person through respiratory droplets (World Health Organization, 2020).It is problematic to imagine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The initial search strategies identified a total of 704 references, which were screened according to the topic of this review. A total of 24 studies (5,10,11,15,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) were finally selected (Figure 1). All the analysed studies were quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search strategies identified a total of 704 references, which were screened according to the topic of this review. A total of 24 studies (5,10,11,15,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) were finally selected (Figure 1). All the analysed studies were quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…This was divided into two parts. Part-I (Demographic characteristics): Included age, gender, nursing qualification, years of experience, work department, residence, marital status, and previous training ( Mohamed et al, 2022 ). Part-II (Knowledge questionnaire): The researcher established this based on El sayed, 2013 to assess staff nurses’ knowledge about SBAR shift reports earlier and later implementing the program.…”
Section: Methodsmentioning
confidence: 99%
“…Part-I (Demographic characteristics): Included age, gender, nursing qualification, years of experience, work department, residence, marital status, and previous training ( Mohamed et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Continued burnout inevitably affects staff work engagement. So far, most studies have concluded a negative correlation between the two (26,27). But work engagement is not only affected by burnout but also by psychological conditions (28), workplace bullying (29), work value perception (30), workfamily balance (31), active motivation, passive motivation and demotivation (32).…”
Section: Introductionmentioning
confidence: 99%